Single motor unit firing behavior in the right trapezius muscle during rapid movement of right or left index finger - Søgaard, Karen; Olsen, Henrik B.; Blangsted, Anne K.; Sjøgaard, Gisela (Frontiers in Human Neuroscience, 2014)
Computer work is associated with low level sustained activity in the trapezius muscle that may cause myalgia. The activity may be attention related or part of a general multijoint motor program providing stabilization of the shoulder girdle for precise finger manipulation. This study examines single motor unit (MU) firing pattern in the right trapezius muscle during fast movements of ipsi or contralateral index finger. Modulated firing rate would support a general multi joint motor program, while a generally increased and continuous firing rate would support attention related activation. 12 healthy female subjects were seated at a computer work place with elbows and forearms supported. Ten double clicks (DC) were performed with right and left index finger on a computer mouse instrumented with a trigger. Surface EMG was recorded from right and left trapezius muscle. Intramuscular EMG was recorded with a quadripolar wire electrode in the right trapezius. Surface EMG was analysed as %MVE. The intramuscular EMG was decomposed into individual MU action potential trains. Instantaneous firing rate (IFR) was calculated from inter-spike interval with ISI shorter than 20 ms defined as doublets. IFR was averaged across 10 DC to show IFR modulation. Surface EMG in both right and left trapezius was 1.8-2.5%MVE. During right hand DC a total of 32 MUs were identified. Four subjects showed no activity. Four showed MU activity with weak or no variations related to the timing of DC. Four subjects showed large modulation in IFR with temporal relation to DC. During left hand DC 15 MUs were identified in 4 subjects, for two of the subjects with IFR modulations related to DC. Doublets was found as an integrated part of MU activation in the trapezius muscle and for one subject temporarily related to DC. In conclusion, DC with ipsi- and contralateral fast movements of the index finger was found to evoke biomechanically as well as attention related activity pattern in the trapezius.